Assesment of Dietary Intake and Anthropometric Parametres Among Rugby Union Players - Dorota Różańska; Justyna Stachura; Katarzyna Żyła (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2014)
The purpose of this study was to evaluate the energy, macronutrient an selected micronutrient intake of second league Rugby Union players and to assess the anthropometric characteristic of this group. Players (n = 44) were divided into forwards (n = 20) and backs (n = 24), who differed significantly in weight (92.6 vs 80.8 kg), BMI (28.6 vs 24.5 kg/m2) and percentage of body fat (22.0 vs 13.3%). The dietary intake was assessed using 3-day dietary recalls. There were no significant differences in dietary intake related to player position. Athletes reported a mean daily energy intake of 3613.4 ±942.6 kcal (carbohydrates 41.4%, protein 17.8%, fats 39.3%). The mean intake of carbohydrates and protein were on a level of 4.8 and 1.9 g/kg of body weight/day, respectively. Although the mean daily intake of minerals and vitamins met recommendations, some players did not reach the requirements, especially for potassium (61.4%) and vitamin C (22.7%). The differences in body compositions of the players suggest differences in the type of training and the specificity of the player’s position. These improper proportions of dietary nutrients within the study group may decrease opportunities to achieve optimum results during matches.